MALFEASANCE AS A SOCAIL PROBLEM AND IT’S PREVENTION - Shvedova, Hanna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to research the phenomenon of malfeasance in Ukraine as a social problem and to identify effective means of general social prevention of malfeasance in modern Ukraine. Methods: a set of general and special methods of scientific knowledge – the terminology, logical-semantic, functional, system-structural, logical and normative. Results: the article considers the legal essence, signs of malfeasance as a social problem, it’s causes and consequences, basic principles of general social prevention of malfeasance in Ukraine. It was found that malfeasance has a high degree of latency, social danger, organization. There are few special social consequences of malfeasance: antisocial orientation of society, acquisition of criminal skills, malfunction of government agencies and criminal activity to be continue. The direction of general social prevention is to ensure the absence of any possibility for the criminal activity and to influence of the inevitability of negative consequences in various ways. Civil society institutions and culturing factors are considered the forward means of general social prevention of malfeasance. Public control over the government agencies can be exercised through the parliament, self-government bodies, mass media, public organizations. A high level of social culture is a key factor in the mechanism of malfeasance. Formation of relations on native laws in a sphere of official activities minimizes the dissemination of malfeasance in society. Such laws include the laws of free competition, equality and non-abuse of rights. Natural laws are formed in the process of society, which rules have to correspond to the modern realities of this society. The members of society are able to open new natural laws on their own, if they are already have the adequate level of social culture. The multifaceted mechanism of legal prevention is considered regular through the parallel introduction of different mechanisms. The modern preventive activity is offered to realize simultaneously in three directions: modernization of the modern legislation, stimulation of lawful behavior and the corresponding law education. Discussion: the ways to improve the institutions of general social prevention of malfeasance in Ukrainian society.